Regulation of GLUT4 biogenesis in muscle: evidence for involvement of AMPK and Ca2+ - Ojuka, Edward O.; Jones, Terry E.; Nolte, Lorraine A.; Chen, May; Wamhoff, Brain R.; Sturek, Micheal; Holloszy, John O. (Am J Physiol Endocrinol Metab 282, 2002)
Regulation of GLUT4 biogenesis in muscle: evidence for involvement of AMPK and Ca2 . Am J Physiol Endocrinol Metab 282: E1008–E1013, 2002; 10.1152/ ajpendo.00512.2001.—There is evidence suggesting that adaptive increases in GLUT4 and mitochondria in skeletal muscle occur in parallel. It has been reported that raising cytosolic Ca2 in myocytes induces increases in mitochondrial enzymes. In this study, we tested the hypothesis that an increase in cytosolic Ca2 induces an increase in GLUT4. We found that raising cytosolic Ca2 by exposing L6 myotubes to 5 mM caffeine for 3 h/day for 5 days induced increases in GLUT4 protein and in myocyte enhancer factor (MEF)2A and MEF2D, which are transcription factors involved in regulating GLUT4 expression. The caffeine-induced increases in GLUT4 and MEF2A and MEF2D were partially blocked by dantrolene, an inhibitor of sarcoplasmic reticulum Ca2 release, and completely blocked by KN93, an inhibitor of Ca2 - calmodulin-dependent protein kinase (CAMK). Caffeine also induced increases in MEF2A, MEF2D, and GLUT4 in rat epitrochlearis muscles incubated with caffeine in culture medium. 5-Aminoimidazole-4-carboxamide ribonucleoside (AICAR), which activates AMP-activated protein kinase (AMPK), also induced approximately twofold increases in GLUT4, MEF2A, and MEF2D in L6 myocytes. Our results provide evidence that increases in cytosolic Ca2 and activation of AMPK, both of which occur in exercising muscle, increase GLUT4 protein in myocytes and skeletal muscle. The data suggest that this effect of Ca2 is mediated by activation of CAMK and indicate that MEF2A and MEF2D are involved in this adaptive response. 5 -adenosine monophosphate-activated protein kinase; gene expression; skeletal muscle; tissue culture; myocyte enhancer factor 2; Ca2 -calmodulin-dependent protein kinase
Keywords: Regulation of GLUT4 biogenesis in muscle